SCC evaluation of composite materials for natural gas absorber based on experimental and numerical methods. (March 2020) - Mou, Yisheng; Lian, Zhanghua; Yu, Hao; Lin, Tiejun; Han, Zihui; Zhang, Qiang
Highlights: In order to obtain the basic data, a series of experiments are carried out. In order to carry out the stress analysis of the absorber in detail. The FEM of WOL sample is established to guide the work is high. To assess the strength of the materials, SCC experiments are carried out. Abstract: Pressure vessel is a primary barrier to gathering system and an important guarantee for normal production in the oilfield. Composite materials for pressure vessels are widely used to adapt to acidic media and temperature and pressure environment. Therefore, the stress corrosion cracking (SCC) is easily caused considering harsh working condition and multi-material structure. Pressure vessel defect due to SCC can cause material strength degradation, medium leakage and even explosion. In order to analyze the stress distribution of the whole equipment and verify the crack detection results in the field, a detailed finite elements model (FEM) of the absorber considering the composite material is established based on mechanical experiments and field data. On the other hand, a WOL specimen FEM is established according to the industry standard. Finally, twelve SCC evaluation experiments of composite materials are carried out based on the results of two established FEM, and the safety windows of 316L and SA516-70 are obtained in specific stress corrosion environments. The work presented in this paper can offer a technological basis and theoretical foundation for strength design of composite materials for pressure vessels in sour environment.